2023
DOI: 10.3390/medicina59101711
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Metabolic Syndrome: A Prospective Study on Cardiovascular Health

Marius Rus,
Simina Crisan,
Felicia Liana Andronie-Cioara
et al.

Abstract: Background and objectives: This article highlights the relationship between metabolic syndrome and cardiovascular disease, providing a comprehensive overview of its risk factors and prevalence. Metabolic syndrome, characterized by a cluster of interconnected risk factors, significantly increases the risk of developing cardiovascular disease and type II diabetes. Materials and methods: This study, conducted over a one-year period, involved 117 patients aged between 30 and 79 years old. Various parameters were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Thus, IR was not always a recognized component of MS. Currently, most authors agree that the incidence of MS is increasing worldwide, and affects 20-30% of the population in developing countries, mainly due to the increasing incidence of obesity and IR [44,45]. This also applies to children, including those born small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IR was not always a recognized component of MS. Currently, most authors agree that the incidence of MS is increasing worldwide, and affects 20-30% of the population in developing countries, mainly due to the increasing incidence of obesity and IR [44,45]. This also applies to children, including those born small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Мариус және т.б. зерттеулерінде МС-ның адам жынысына қарай эпидемиологиясы 2022 жылдың қаңтары -2023 жылдың ақпаны арасында 63,3% құрағаны және әйелдермен салыстырғанда ерлерде бұл синдромның жиі кездесетіні анықталды [11,12]. Когнитивтік және психосоматикалық бұзылыстар әлемдегі мүгедектіктің негізгі себептерінің бірі болып табылады және жалпы популяциядағы МС-ның қаупін екі есе арттырды [14,15].…”
Section: кіріспеunclassified
“…According to the United States National Health and Nutrition Examination Survey (NHANES), over one third adults exhibit MetS, and the incidence rate among middle-aged and elderly people aged 40 and older is as high as 40% ( 2 ). MetS is particularly detrimental to middle-aged and elderly people, and some studies mainly composed of middle-aged and elderly people have suggested that MetS is associated with adverse cardiovascular risk and mortality ( 2 , 3 ). At present, there are no MetS-targeting medications ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…MetS is particularly detrimental to middle-aged and elderly people, and some studies mainly composed of middle-aged and elderly people have suggested that MetS is associated with adverse cardiovascular risk and mortality ( 2 , 3 ). At present, there are no MetS-targeting medications ( 3 ). Considering that MetS is closely correlated with cardiovascular disease ( 4 ), proper MetS management can potentially enhance cardio vascular health (CVH).…”
Section: Introductionmentioning
confidence: 99%